STUDI NILAI KUAT GESER TANAH LUNAK BERDASARKAN BESARNYA PENURUNAN YANG TERJADI - Istiatun Istiatun; Handi Sudardja; Yuwono Yuwono (Construction and Material Journal, 2021)
Soft soil is not suitable for supporting construction that stands on it because it has low shaman power, high compressive properties, and little stability. The compressibility of the soil certainly affects the existing construction, especially if the settlement that occurs due to the compression of the soil is not permitted. While the low bearing capacity of the soil causes the design load cannot be carried out directly, it is generally given in stages. The advantage of providing the load that gradually causes the density of the soil will increase. The soil with increased density will increase the carrying capacity of the soil so that it can accept the load of the next stage. Increasing in bearing capacity is given due to the magnitude of the land subsidence that occurs. It is necessary to test with laboratory modeling. Soil samples were put in the test basin and given additional water to determine how things were in the field if the soil experienced an increase in water content. Soil samples were loaded and recorded the amount of settlement that occurred. Increasing bearing capacity by conducting direct shear test changes in the soil bearing capacity parameter values is known to correlate the magnitude of the decrease in soil that occurs. In addition, an analysis of changes in water content and soil volume weight was also carried out due to the magnitude of the decrease. From the test modeling results in the laboratory with a test basin, it was found that the greater the value of soil subsidence, the higher the cohesion value of the soil and the lower the shear angle in the soil. For soil, water content is inversely proportional to the decrease, the more significant the decrease, the smaller the water content. Meanwhile, the weight of the soil volume is directly proportional; the more significant the decrease that occurs, the greater the weight of the volume of the soil. Keywords: Settlement, Shear Strength Parameter, Soft Soil, Direct Shear Test.